ESIPT-based fluorescence probe for the rapid detection of hypochlorite (HOCl/ClO−). Issue 61 (16th July 2018) - Wu, Luling; Yang, Qingye; Liu, Liyuan; Sedgwick, Adam C.; Cresswell, Alexander J.; Bull, Steven D.; Huang, Chusen; James, Tony D.
Abstract : ESIPT-based fluorescence probes are emerging as an attractive tool for the detection of biologically relevant analytes owing to their unique photophysical properties. Abstract : ESIPT-based fluorescence probes are emerging as an attractive tool for the detection of biologically relevant analytes owing to their unique photophysical properties. In this work, we have developed an ESIPT-based fluorescence probe (TCBT-OMe ) for the detection of HClO/ClO − through the attachment of a bioorthogonal dimethylthiocarbamate linker.TCBT-OMe was shown to rapidly detect HClO/ClO − (<10 s) at biologically relevant concentrations (LoD = 0.16 nM) and have an excellent selectivity towards others ROS/RNS and amino acids. Therefore, TCBT-OMe was tested in live cells and was successfully shown to be able to detect endogenous and exogenous HClO/ClO − in HeLa cells. Additionally, TCBT-OMe acts as a dual input logic gate for Hg 2+ and H2 O2 . Interestingly, Hg 2+ alone gradually causes a fluorescence response but requires >30 min to produce a fluorescence response. Test strips containingTCBT-OMe were prepared and were demonstrated as an effective way to detect HClO/ClO − in water. Furthermore, TCBT-OMe was shown to detect exogenously added HClO/ClO − in three different water samples with little interference thus demonstrating the effectiveness as a method for the detection of HClO/ClO − in drinking water samples.